Color Removal of Textile Wastewater Using Electrochemical Batch Recirculation Tubular Upflow Cell - Ammar A. Beddai; Basma Abdulhadi Badday; Atheer M. Al-Yaqoobi; Mohanad Kadhim Mejbel; Zainab S. Al Hachim; Mustafa K. A. Mohammed (International Journal of Chemical Engineering)
The progress in textile industrial technologies comes along with a massive increase in the discharge of dyes in the wastewater which considers a serious environmental problem. In this regard, a new electrochemical system has been developed for the treatment of simulated dye solutions of permanent methylene blue dye by an electrochemical cyclic ring reactor. An aluminum rod and a stainless steel mesh were used as the anode and cathode. The experiments on the artificial dye solutions have been carried out in a 6-liter electrochemical cell containing 50 ppm neutral dye solutions. The effects of various parameters such as electrolysis time applied current density (2, 3.32, 5.31, 6.64, and 7.46 mA cm−2), electrolyte concentrations (600, 900, 1200, 1500, and 1800 ppm), and flow rates (1, 1.5, 2, 2.5, and 3 Lh−1) on the process removal efficiency were examined. The results demonstrated that the removal efficiency reached 94–99% within 40–50 minutes of electrolysis time. The removal efficiency increased by increasing the flow rates until it reaches a maximum value at a flow rate of 2 Lh−1; thereafter, it declined with the farther augment of recirculation speed. It is indicated that raising the applied current resulted in increasing the removal efficiency. However, the power consumption builds up to the maximum value by increasing the applied current, where the power consumption rose from 8.51 to 30.3 kWh kg−1 with an increase in the current density from 2 to 7.46 mA cm−2, and a removal efficiency increased from 94% to 99%, accordingly. The results also showed that by increasing the electrolyte concentration, the power consumption can be reduced to its minimum value and the removal efficiency increased remarkably.